Handedness and specific language impairment: a study of 6-year-old twins - Bishop, D (Wiley, 2005)
Handedness and language skills were assessed in 196 same-sex twin pairs (101 MZ and 95 DZ), who were selected from an epidemiological study of twins, so that children with risk of language impairment were over-represented. When assessed at 6 years of age, 83 children met criteria for specific language impairment (SLI), 32 had general developmental (GD) delay, and the remaining 277 were typically-developing (TD). Hand preference (HP) assessed by inventory did not distinguish SLI, TD, or GD groups. The quantification of hand preference (QHP) measure, which measures persistence of a HP when reaching across the midline, did show weaker HP in those with SLI compared to the other two groups. It is suggested that the QHP measure assesses developmental aspects of manual lateralization, and is sensitive to neurodevelopmental immaturity in SLI. Furthermore, genetic analysis showed that the QHP measure, unlike the handedness inventory, was significantly heritable.